Tracing the Existence of Education and Training Participants - Mokhlis; Heni Listiana; Hamdani; Nuri Wahda Salsabila Usmany (Amandemen: Journal of Learning, Teaching and Educational Studies, 2025)
Education and training participants are an image where a person has changes after attending the training itself. This can be pursued with the abilities managed by the teacher according to their field of competence, because the teacher's task is not only about thinking about how the material is delivered, but also how the material provided can be influence the productivity of training participants. The objectives of this research are three things, 1) knowing the participants' expectations, 2) knowing the encouragement and motivation, and 3) knowing the performance and learning patterns of the training participants. This research uses the library research method, the primary source comes from a study of the existence of educational training participants, while the secondary data source comes from the same study or is related to this research, whether in the form of books, journals, articles, theses and other literature. . The results of this research are that: 1) the expectations of training participants can be grouped into three, namely expectations, values ​​and relationships. 2) The participants' encouragement and motivation are divided into three, namely the desire to know/learn, the need to learn and the desire for future goals. 3) Changes in participants' performance can be seen from three things, namely response, change and results.